Revitalisasi Dolanan Anak Iringan Gejog Lesung sebagai Inovasi Pendidikan Sendratasik di Sanggar Seni Langgeng Budoyo - Salsabila, Fairuz Inas Tsabitah; Yusarianti, Alvina; Arif Anandhita, Nur (JPKS (Jurnal Pendidikan dan Kajian Seni), 2024)
Traditional arts are increasingly being eroded and people are no longer interested in them. What a shame it is for the nation's next generation to only use sophisticated technology, without knowing the function of technology. So you won't get anything. Like today's children who continue to play with gadgets and reduce social interaction in society. So revitalization measures are needed to re-learn traditional arts. In particular, for children, revitalization of traditional arts will be provided through the performing arts Dolanan Anak Iringan Gejog Lesung. With this performing art, people of all ages, from children to adults, can enjoy it. This performing art is a traditional art from the Bantul Regency area, and this art was developed by the Langgeng Budoyo Art Studio. From the revitalization process carried out by the studio, new innovations in education can emerge. Initially, the studio only trained dance, but now it can train all three fields of art, namely drama, dance and music. So that the extinction and erosion of traditional arts can be prevented by children's interest in art and having aesthetic experiences that become provisions for social life.